EFEKTIVITAS HERBAL CREAM MASSAGE KOMBINASI SEREH DAN KENCUR TERHADAP PENURUNAN NYERI IBU BERSALIN - Nur Aini; Hidayat Wijayanegara; Meti Widiya Lestari; Herri S Sastramihardja; Anita Deborah Anwar; Ma’mun Sutisna (Jurnal Medikes (Media Informasi Kesehatan), 2025)
Labor is a manifestation of uterine muscle contractions. Efforts to overcome pain are by non-pharmacological methods with “Herbal Cream massage BundaCare” is one product that utilizes natural ingredients from plants such as kencur (Kaempferia galanga) and lemongrass (Cymbopogon citratus) to help reduce pain in laboring mothers. The purpose of this study was to analyze the effectiveness of massage with “Herbal Cream Massage Bundacare” compared to massage therapy alone on reducing pain in laboring women at Made Surya Cipayung Midwife Independent Practice. This type of research is a quasi-experiment (pseudo-experiment) with a two group pretest-post test design approach, the total sample of 84 laboring women in the first phase of the active phase is divided into intervention (BundaCare) and control (regular massage) groups. The research was conducted at Made Cipayung Midwife Independent Practice Center, East Jakarta on October 24, 2024-December 24, 2024. Sampling using accidental sampling and measuring pain with NRS (Numeric Rate Scales). Univariate analysis of respondent characteristics using descriptive statistics. Bivariate test using Wilcoxon test and Independent T test and effectiveness test using Gain score. The results of statistical tests using the Wilcoxon test showed a significant decrease in pain in both groups (p<0.05). The BundaCare group experienced a decrease from moderate to mild pain, while the regular massage group remained at moderate pain. The results of the effectiveness test in the “Herbal cream massage Bundacare” group obtained a Gain score of 68% which means the category is quite effective while in the massage therapy group alone obtained a Gain score of 40% which is included in the less effective category. In conclusion, there is a difference in reducing labor pain between massage therapy with “Herbal cream massage Bundacare” compared to massage therapy alone and “Herbal cream massage Bundacare” therapy is more effective in reducing labor pain compared to massage therapy alone at the Made Cipayung Midwife Independent Practice Place, East Jakarta, 2024.